Experimental search for interference effects in the total e− + Sc3+ recombination rate - Schippers, Stefan; Bartsch, T.; Brandau, C.; Müller, A.; Linkemann, J.; Saghiri, Amir Ahmad; Wolf, Andreas (Physical review. A, Atomic, molecular, and optical physics, 1999)
In a recent theoretical paper Gorczyca et al. [Phys. Rev. A 56, 4742 (1997)] predicted interference between radiative and dielectronic recombination to show up in the total recombination rate coefficient of Ar-like Sc3+(3s23p6) with the signature of interference being an asymmetric line profile of the 3s23p53d22F dielectronic recombination resonance. Due to limited counting statistics our experimental result obtained at the Test Storage Ring at the Heidelberg Max-Planck-Institut for Nuclear Physics does not permit a detailed line-shape analysis to be carried out. However, differences between theory and experiment remain to be explained.